Contrast diversity patterns and processes of microbial community assembly in a river-lake continuum across a catchment scale in northwestern China - Xiangming Tang; Guijuan Xie; Keqiang Shao; Yang Hu; Jian Cai; Chengrong Bai; Yi Gong; Guang Gao (Environmental Microbiome, 2020)
Abstract Background Microorganisms in rivers and lakes are essential for nutrient recycling in aquatic ecosystems. Understanding the ecological processes shaping microbial communities is of crucial importance for aquatic microbial ecology and biogeography. However, the diversity of microorganisms and the forces that control this diversity are poorly understood. This is particularly true within the framework of the river-lake continuum in arid regions. Results Using a whole catchment-sampling effort, we explored biogeographical patterns and mechanisms of microbial community (bacteria and archaea) assembly within the catchment of the largest inland once freshwater lake (Lake Bosten) in China. Water samples from headstream tributaries, the mainstream of the River Kaidu to downstream Lake Bosten were characterized using amplicon sequencing of 16S rRNA genes. Higher α-diversity was found in mainstream of River Kaidu and in the tributaries compared with Lake Bosten. And the microbial community composition was also significantly different between the lake and its connected river habitats. Canonical correspondence analysis demonstrated that salinity and total suspended solids were the most important environmental factors shaping the community variations. Overall, pure environmental and pure spatial factors explained 13.7 and 5.6% of the community variation, respectively, while 32.0% of the variation was explained by combined environmental and spatial variables. These observations suggested that spatially structured environmental variations mainly shaped the microbial biogeography in this region. Both deterministic and stochastic processes influenced the microbial community assembly in river and lake habitats, and the stochastic pattern was particularly pronounced for microbiome in river habitat. Co-occurrence network analysis revealed more abundant and complicated correlations among frequently occurred taxa in lake habitat compared with the river habitat, implying that ecological multispecies interactions (e.g., competition) shaped lake microbial community structures. Conclusions Our findings demonstrate an ecological succession along the river-lake continuum of microbial communities across the largest inland once freshwater lake basin in China, and highlight the effects of spatially structured environmental factors on regional microbial β-diversity and species interactions on local community assembly.